Experiments in postcolonial reading: music, violence, response - Venter, C (2015)
This thesis is a response to a lacuna in musicology, namely the near absence of postcolonial and decolonial epistemologies. Employing both diachronic and synchronic perspectives, it provides a historical overview of the institutional positioning of musicology as an academic discipline founded on structures of expectation and exploitation indebted to Western imperialism. This longer historical view is accompanied throughout by an examination of ethics in its institutionalised forms, specifically in the domains of knowledge production and the university. The thesis maintains that while such ostensibly ethical underpinnings may promise redress on the basis of the violence inflicted by an imperialist past, the discourse employed in its application in fact serves to strengthen the ideological hold of Western hegemony and, in so doing, betrays the promise of reparation that ethics is ordinarily understood to encompass. The thesis examines different aesthetic and epistemological manifestations of the postcolonial, considering at length Steve Reich’s string quartet, Different Trains (1988), Philip Glass's opera, Waiting for the Barbarians (2005), and Philip Miller’s choral work, REwind: A Cantata for Voice, Tape and Testimony (2006). Both content and style weave these works together as they engage, by means of a post-minimalist aesthetic, stream-of-violence narratives intimately bound up with the postcolonial condition. Of particular importance in the consideration of these musical texts is the urgent necessity for epistemological transformation, marked in musicology as the lack of post- and decolonial perspectives. Finally, the thesis grapples with the (im)possibility of complicit scholarship that must, through its very expression, wound its subject.